Splenorenal shunt via magnetic compression technique: a feasibility study in canine and cadaver. Issue 6 (1st November 2016) - Xue, Fei; Li, Jianpeng; Lu, Jianwen; Zhu, Haoyang; Liu, Wenyan; Zhang, Hongke; Yang, Huan; Guo, Hongchang; Lv, Yi
Abstract: Introduction: The concept of magnetic compression technique (MCT) has been accepted by surgeons to solve a variety of surgical problems. In this study, we attempted to explore the feasibility of a splenorenal shunt using MCT in canine and cadaver. Material and methods: The diameters of the splenic vein (SV), the left renal vein (LRV), and the vertical interval between them, were measured in computer tomography (CT) images obtained from 30 patients with portal hypertension and in 20 adult cadavers. The magnetic devices used for the splenorenal shunt were then manufactured based on the anatomic parameters measured above. The observation of the anatomical structure showed there were no special structural tissues or any important organs between SV and LRV. Then the magnetic compression splenorenal shunt procedure was performed in three dogs and five cadavers. Seven days later, the necrotic tissue between the two magnets was shed and the magnets were removed with the anchor wire. Results: The feasibility of splenorenal shunt via MCT was successfully shown in both canine and cadaver, thus providing a theoretical support for future clinical application.